Discrete tensor product BGG sequences: splines and finite elements - Bonizzoni, Francesca; Hu, Kaibo; Kanschat, Guido; Sap, Duygu (Mathematics of computation, 2024)
In this paper, we provide a systematic discretization of the Bernstein-Gelfand-Gelfand diagrams and complexes over cubical meshes in arbitrary dimension via the use of tensor product structures of one-dimensional piecewise-polynomial spaces, such as spline and finite element spaces. We demonstrate the construction of the Hessian, the elasticity, and complexes as examples for our construction.
Gesehen am 23.10.2024